Exploring Parking as a contributor to financial sustainability of urban transport - Chauhan, Varsha (SPA Bhopal, 2024)
As the world gets more urbanized by the day, legislators and urban planners are becoming increasingly concerned about efficient parking management. This study, which focuses on a particular Municipal Corporation of Delhi (MCD) zone, is to investigate the possibilities of parking as a revenue-generating instrument in urban transport planning. Managing parking resources has become an essential part of urban development, rather than only a logistical task, as private vehicle ownership and urbanization have increased. It is essential to comprehend how pricing techniques affect parking management dynamics in order to advance financial sustainability and improve the standard of urban living. Analysing current parking issues and trends, comprehending the connection between accessibility of public transportation and parking demand, pinpointing important variables affecting parking demand and usage patterns, and formulating plans to maximize parking as a source of income and encourage modal shift in urban transportation planning are some of the goals of the study. These goals will be met by doing a comprehensive study of the parking environment, looking into problems unique to the chosen MCD zone, and researching innovative management strategies. Major parking issues arise in large cities due to the quick growth in parking generation rate that comes with continued expansion. The study will offer insights into the financial viability of parking projects by evaluating current parking policies and financial models. Along with examining the effects of shared parking arrangements and dynamic pricing, it will provide intelligent recommendations for boosting revenue generation and easing traffic congestion. The study has been conducted to examine parking features and gauge compliance with parking regulations. Eight portions in Delhi have had parking studies completed; these sections usually comprised PSP, commercial and residential land use. Focusing on several parking data metrics, the analysis of parking characteristics was carried out, both on-street and off-street. These included the number of cars parked in a space, the load of cars compared to the number of spaces available, the amount of time cars spends parked on average, Exploring Parking as a Contributor to Financial Sustainability of Urban Transport and the parking index, or efficiency of parking utilization. The investigation showed that traffic problems persisted even in places where there appeared to be adequate parking. This was frequently linked to ineffective parking management techniques, such as a lack of effective parking tactics, a lack of properly marked parking places, and a lack of the required signage to guide cars to available spaces. These results emphasize how crucial efficient parking management is in cities. In order to reduce traffic and enhance the entire parking experience for drivers, parking efficiency measures including improved signage, clearly marked spaces, and creative parking solutions can be put into practice. The purpose of the study is to determine whether parking can be used as a reliable source of income and as a way to relieve traffic in cities. It aims to show how parking may be managed to reduce problems with urban transportation and make a major contribution to the financial elements of urban transportation planning through thorough study and evaluation. The study's inclusion of various scenarios for parking price justification based on land value, metro-set minimum costs, and public willingness to pay for rising amounts is critical for understanding parking management dynamics. The goal in studying these scenarios is to provide insights into how parking might be managed successfully to decrease congestion and contribute to long-term urban growth. For example, higher parking fees in high-value neighbourhoods or near metro stations might encourage the use of public transportation or shared mobility options, lowering the number of private automobiles on the road and alleviating congestion. The results of this study will, in general, add to the body of knowledge on urban mobility planning and offer useful suggestions to help planners and policymakers better manage parking resources, encourage sustainable urban growth, and improve urban quality of life.
Keywords: Urban transport; Car Parking; Parking Planning